Self-esteem and Defensiveness. Healthy Interactive Ingredients with the Partner? - Sánchez Aragón, Rozzana; Díaz Loving, Rodolfo (Revista de Psicología, 2002)
Personality factors such as self esteem and defensiveness are fundamental to the development of interpersonal relationships. Research shows self-acceptance, selfesteem and secure attachment styles lead to more, and richer, longer and more satisfying relationships. At the same time, an avoidant attachment style and insecurity are precursors of rejection, anxiety and dislike in relationships, leading to low satisfaction and lack of positive behaviors (Meyers & Landsberger, 2002). In the present study, measures of self esteem, defensiveness, attachment styles and reasons to be in a relationship where used to predict satisfaction in the relationship and then all variables to predict positive and negative behaviors. A sample of 431 Mexican adult subjects in relationships received all measures. Results show a tight coherence between self esteem and security, as well as the central role of emotional security, satisfaction with emotional aspects of the relationship, secure attachment and being in the relationship because of love in the disposition of positive behaviors such as recognizing the positive qualities of partner, helping, cuddling, laughing together etc.